A INFÂNCIA, O BRINCAR E A CULTURA ESCOLAR NA PRÉ-ESCOLA: um estudo da prática lúdica na Unidade de Educação Básica Mary Serrão Ewerton, em São Luís/MA - GUTERRES, Ione da Silva (2022)
This research is about the interweaving of threads with playful perspectives that emphasize the cultures of childhood and play in the playful practices of a public preschool in the rural area of São Luís, MA. The research came from the following problem: How to weave the threads of playful perspectives in the school culture of young children belonging to the public municipal network in the rural area of São Luís, MA, prioritizing the culture of childhood and play in the educators' playful practices, in order to elaborate a Pedagogical Guidelines Booklet that emphasizes play as a specific language of childhood? In view of this concern, the following guiding questions arose: what are the theoretical and methodological conceptions that guide the playful practices of Kindergarten I and II educators? In what playful situations, play and games can establish relationships between the dimensions of being a child and living childhood? How can a formative meeting be organized with the educators in order to prioritize the play in the ludic practices? How can the researcher, in partnership with the educators at the Mary Serrão Ewerton Basic Education Unit, prepare a Pedagogical Guidance Booklet with games, toys, and games that prioritize the knowledge of children as something proper to the school culture? Through these questions, the general objective of this research was to interweave the threads of playful perspectives in the school culture of young children belonging to the municipal public network in the rural area of São Luís-MA, prioritizing the culture of childhood and play in the educators' playful practices, with a view to preparing a Pedagogical Guidance Booklet that emphasizes play as a specific language of childhood. As an unfolding, the following specific objectives were established To verify the theoretical and methodological conceptions that guide the playful practices of Kindergarten I and II educators; to understand in which playful situations the game, the toy and the game could establish relations between the dimensions of being a child and living childhood; to carry out formative meetings with the educators in order to prioritize the play in playful practices; to elaborate, in collaboration with the educators, a Pedagogical Guidelines Handbook with games, toys and games that emphasize the knowledge of children as something proper to school culture. To give theoretical basis to this research, scholars and researchers in the area were revisited, such as: Ariès (2019), Kuhlmann Junior (2015), Freitas (2007), Faria (2007; 2011), Quinteiro (2002), Corsaro (2011), Brougère (2010), Kishimoto (2011), Friedmann (2012), among others. As methodology, the state-of-the-art literature review and the pedagogical intervention were used, with a qualitative focus; from the point of view of the objectives, it was classified as exploratory research. The research subjects were four preschool educators and one manager. The data production tools used were: participant observation of the pedagogical work routine of each educator in the planning group and in the class where she works, and semi-structured interviews with the school manager and four educators. The data analysis technique used was content analysis. During the research, a subtle tension was observed between the educators' understanding of the need to play and the parents' demand that they teach the so-called school contents. However, the practice of play stands out from this tension between childhood culture and school culture in the investigated institution, because the teachers' actions revealed the importance of and priority for play in educational activities. Thus, the expectation is that the findings can serve as indicators for the improvement of teaching actions, considering children as active, historical and subjects of rights, social actors who produce culture in interactions.